Ovarian Aging: Role of Pituitary-Ovarian Axis Hormones and ncRNAs in Regulating Ovarian Mitochondrial Activity - Colella, Marco; Cuomo, Danila; Peluso, Teresa; Falanga, Ilaria; Mallardo, Massimo; De Felice, Mario; Ambrosino, Concetta (Frontiers in Endocrinology, 2021)
Unbalance of the circulating levels of the hormones active along the pituitary-ovarian axis (gonadotropins, estrogens, AMH and other ovarian peptides) is the biochemical signs of physiological or premature ovarian aging. Mitochondria are key players of the apoptosis of ovarian germ and somatic cells and they are essential sites of the synthesis of sex steroid. They are also targets of estrogens and of gonadotropin-dependent signaling pathways. Therefore, understanding the mechanisms by which ovarian hormones and pituitary gonadotropins regulate mitochondrial dynamics and activity, including sex hormones production, is pivotal to molecularly define the role of mitochondrial dysfunction in the physiological and premature ovarian aging. The estrogen and of gonadotropin-dependent signaling pathways also modulate the cellular content of ncRNAs involved in ovarian aging. We will provide insight into ncRNAs as mediators of the effects of these signaling pathways on mitochondria function and dynamic in the context of either physiological or premature ovarian aging, highlighting their roles in altered production of female steroid hormones, in energy production and mitochondrial scavenger activity. We will focus on the miRNAs and the lncRNAs, shown to be altered in models of physiological and premature ovarian aging, trying to reveal their regulatory activity in the crosstalk between mitochondria/pituitary-ovarian hormone dependent pathways in the ovary. Furthermore, we will propose a role for the mitochondrial ncRNAs (mitomiRs, mtlncRNAs), that retranslocate from the mitochondria to the nucleus as active player of the mitochondria-nuclei crosstalk impaired in aging. The full understanding of the mechanisms tuning the mitochondrial function and dynamics by signaling pathways responding to hormones active along the pituitary-ovarian axis is essential to propose them as potential diagnostic markers and/or therapeutic targets for ovarian aging diseases.